Large-Scale Trial of Question Web Learning in Physics to Enhance Students’ Scientific Questioning Skills - Evendi, Evendi; Wahyuni, Agus; Ngadimin, Ngadimin; Yakob, Muhammad; Suyidno, Suyidno (IJORER : International Journal of Recent Educational Research, 2026)
Objective: Students’ scientific questioning skills are essential in inquiry-oriented physics learning. However, many high school students still hesitate to ask questions and experience difficulty formulating testable scientific questions. This study aimed to examine a large-scale trial of the Question Web Learning model in physics learning to enhance students’ scientific questioning skills. Method: This study was part of educational design research and employed a one-group pretest-posttest design during the assessment phase. The participants were 93 grade XI science students from 3 public senior high schools in Banda Aceh, Indonesia. Data were collected through classroom observations, a written scientific questioning skills test, field notes, and student response questionnaires. The data were analyzed descriptively using implementation categories, question-quality categories, normalized gain, and response percentages. Results: he findings showed that the Question Web Learning model was implemented in good to very good categories across five meetings in the three schools. Students’ written test scores increased from the scientific category before learning to the very scientific category after learning, with high normalized gain in all schools. Classroom observations also showed an increase in the number and quality of students’ questions, with no non-scientific questions recorded. Novelty: This study provides empirical evidence from a large-scale trial that Question Web Learning is a practical and effective for supporting students’ scientific questioning skills in high school physics learning.